Reporters on the Battlefield - Paul, Christopher; Kim, James J. (RAND Corporation, 2023)
Focusing on the embedded press system deployed during Operation Iraqi Freedom, this book attempts to answer the following questions: How effective was the embedded press system in meeting the needs of the three main constituencies-the press, the military, and the citizens of the United States? What policy history led to the innovation of an embedded press system? Where are press-military relations likely to go in the future?